2020
DOI: 10.3390/ma13184149
|View full text |Cite
|
Sign up to set email alerts
|

Time-Stability Dispersion of MWCNTs for the Improvement of Mechanical Properties of Portland Cement Specimens

Abstract: This study shows the energy optimization and stabilization in the time of solutions composed of H2O + TX-100 + Multi-Wall Carbon Nanotubes (MWCNTs), used to improve the mechanical properties of Portland cement pastes. For developing this research, sonication energies at 90, 190, 290, 340, 390, 440, 490 and 590 J/g are applied to a colloidal substance (MWCNTs/TX-100 + H2O) with a molarity of 10 mM. Raman spectroscopy analyses showed that, for energies greater than 440 J/g, there are ruptures and fragmentation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 51 publications
(63 reference statements)
0
6
0
Order By: Relevance
“…This curing setup is presented in Figure 2. At the end of the curing process, the cement paste cylinders were placed into an oven at 40 °C for 24 h to remove excess water in the pores of the composite [34].…”
Section: Au Nps-cement Composites Fabricationmentioning
confidence: 99%
“…This curing setup is presented in Figure 2. At the end of the curing process, the cement paste cylinders were placed into an oven at 40 °C for 24 h to remove excess water in the pores of the composite [34].…”
Section: Au Nps-cement Composites Fabricationmentioning
confidence: 99%
“…Some experiments have confirmed that MWCNTs can be effectively dispersed in water using ultrasound energy and commercial surfactants [11][12][13]. In the literature, it is possible to observe works focused on applying surfactants to sustain the dispersion [14]. For example, Mendoza [15] studied several dispersion concentrations of surfactants such as sodium lauryl sulfate, cetylpyridinium chloride, and Triton X-100, finding that the reinforcing effect of MWCNTs is masked by the negative effect of the surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…The setting of favorable conditions for effective hydration can be reached by the application of ultrafine additives with high surface activity caused by their small size. Among such additives, it is possible to mention carbon-based nanomaterials such as carbon black [14][15][16][17], isostatic graphite [18][19][20], graphene oxide [21,22], graphene nanoplatelets [23,24], carbon nanotubes [25][26][27], and carbon fibers [28,29]. The listed additives possess several unique properties, such as high surface energy, mechanical strength, and electrical conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…The listed additives possess several unique properties, such as high surface energy, mechanical strength, and electrical conductivity. The application of such additives for the modification of composites provides an improvement in the structure of the binding matrix and, consequently, leads to the improvement of different composite properties [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation